1987
DOI: 10.1103/physrevlett.58.1460
|View full text |Cite
|
Sign up to set email alerts
|

Simple x-ray standing-wave technique and its application to the investigation of the Cu(111) ( √3 √3 )R30°-Cl structure

Abstract: A new variant of the usual x-ray standing-wave experiment, scanning the Bragg reflection in energy at normal incidence, is shown to be applicable to metal crystals without special precautions being taken to ensure high crystalline perfection. The structure of the Cu(l 1 l)(V3x VJ)i?30°-Cl chemisorption phase is found to be compatible with the results of a previous surface extended x-ray-absorption fine structure and photoelectron diffraction study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(39 citation statements)
references
References 18 publications
5
34
0
Order By: Relevance
“…Due to extreme broadening of the Darwin curve in the first case (the half-width of the curve ∆θ 1/2 in this case is proportional to √ χ h ) this conditions of generating XSW can be effectively applied for less perfect for e.g. mosaic crystals (see for modifications of the dynamical theory [145,146] and for XSW measurements [147,148,149,150] and also review paper [23]). …”
Section: Discussionmentioning
confidence: 99%
“…Due to extreme broadening of the Darwin curve in the first case (the half-width of the curve ∆θ 1/2 in this case is proportional to √ χ h ) this conditions of generating XSW can be effectively applied for less perfect for e.g. mosaic crystals (see for modifications of the dynamical theory [145,146] and for XSW measurements [147,148,149,150] and also review paper [23]). …”
Section: Discussionmentioning
confidence: 99%
“…Copper has an fcc structure (space group 225) whose optimised lattice paramenter is 3.63Å (experimental lattice parameter is 3.60Å [17]). These parameters were used for all the calculations reported here.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Motivated by its diverse application, the chlorine-copper interaction has attracted great deal of experimental [8][9][10][11][12][13][14] and theoretical [15][16][17][18] studies. Mounting experimental evidence shows a strong interaction between Cl and Cu atoms as evident from electron diffraction (LEED) [8], normal-incident X-ray standing wave (NIXSW) [9], surfaceextended X-ray adsorption fine structure (SEXAFS) [10,11], shadow-cone-enhanced secondary-ion mass spectrometry (SIMS) [6,12], and Scanning Tunnelling microscopy (STM) [13,14] methods. STM studies found that the chlorine molecules adsorb dissociatively on the Cu(111) surface, leading to formation of various well-ordered phases.…”
Section: Introductionmentioning
confidence: 99%